Synergetic effect of yeast cell-surface expression of cellulase and expansin-like protein on direct ethanol production from cellulose - Nakatani, Yuki (BioMed Central, 2013)
BACKGROUND: Numerous studies have examined the direct fermentation of cellulosic materials by cellulase-expressing yeast; however, ethanol productivity in these systems has not yet reached an industrial level. Certain microorganisms, such as the cellulolytic fungus Trichoderma reesei, produce expansin-like proteins, which have a cellulose-loosening effect that may increase the breakdown of cellulose. Here, to improve the direct conversion of cellulose to ethanol, yeast Saccharomyces cerevisiae co-displaying cellulase and expansin-like protein on the cell surface were constructed and examined for direct ethanol fermentation performance. RESULTS: The cellulase and expansin-like protein co-expressing strain showed 246 mU/g-wet cell of phosphoric acid swollen cellulose (PASC) degradation activity, which corresponded to 2.9-fold higher activity than that of a cellulase-expressing strain. This result clearly demonstrated that yeast cell-surface expressed cellulase and expansin-like protein act synergistically to breakdown cellulose. In fermentation experiments examining direct ethanol production from PASC, the cellulase and expansin-like protein co-expressing strain produced 3.4 g/L ethanol after 96 h of fermentation, a concentration that was 1.4-fold higher than that achieved by the cellulase-expressing strain (2.5 g/L). CONCLUSIONS: The PASC degradation and fermentation ability of an engineered yeast strain was markedly improved by co-expressing cellulase and expansin-like protein on the cell surface. To our knowledge, this is the first report to demonstrate the synergetic effect of co-expressing cellulase and expansin-like protein on a yeast cell surface, which may be a promising strategy for constructing direct ethanol fermenting yeast from cellulose.